The Future Is Not What It Used to Be : Climate Change and Energy Scarcity - Friedrichs, Jörg (Book collections on Project MUSE., 2013)
In this book, the author argues that industrial society itself is transitory, and examines the prospects for our civilization's coming to terms with its two most imminent choke points: climate change and energy scarcity. The author contends that industrial civilization cannot outlast our ability to burn fossil fuels and that the demise of industrial society would entail cataclysmic change, including population decreases. To understand the social and political implications, the author examines historical cases of climate stress and energy scarcity: devastating droughts in the ancient Near East; the Little Ice Age in the medieval Far North; the Japanese struggle to prevent 'fuel starvation' from 1918 to 1945; the 'totalitarian retrenchment' of the North Korean governing class after the end of Soviet oil deliveries; and Cuba's socioeconomic adaptation to fuel scarcity in the 1990s. The warnings of climate scientists are met by denial and inaction, while energy experts offer little guidance on the effects of future scarcity. The book suggests that to confront this predicament society must affirm its core values. Whether we are private citizens or public officials, complacency is not an option: climate change and energy scarcity are emerging facts of life.--adapted from publisher's description.